2014
DOI: 10.1016/j.urolonc.2012.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic validation of renal cell carcinoma histology in the Surveillance, Epidemiology, and End Results program

Abstract: Purpose The Surveillance, Epidemiology, and End Results (SEER) program is an important epidemiologic research tool to study cancer. No information is available on its pathologic accuracy for renal cell carcinoma (RCC). Methods Central pathology review was analyzed as a part of the United States Kidney Cancer Study. Cases previously identified through the Detroit SEER registry were reviewed. The sensitivity and specificity, and positive and negative predictive values were calculated for each SEER-assigned sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2017
2017
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 16 publications
0
17
0
2
Order By: Relevance
“…To account for this, we have limited our analyses to patients in whom a specific histologic type consistent with RCC was noted (ie, clear cell, papillary, and chromophobe). A recent study by Shuch et al 17 suggested that these diagnoses were recorded in SEER with substantial precision. Missing data are another issue in SEER, with several variables relevant to RCC not recorded.…”
Section: Discussionmentioning
confidence: 99%
“…To account for this, we have limited our analyses to patients in whom a specific histologic type consistent with RCC was noted (ie, clear cell, papillary, and chromophobe). A recent study by Shuch et al 17 suggested that these diagnoses were recorded in SEER with substantial precision. Missing data are another issue in SEER, with several variables relevant to RCC not recorded.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with multiple second diagnoses of kidney cancer, the earliest diagnosis was used as the reference. Previously published International Classification of Diseases for Oncology (3rd edition) histologic/behavior codes were used to classify patients with RCC . Only microscopically confirmed cases of RCC were included.…”
Section: Methodsmentioning
confidence: 99%
“…Previously published International Classification of Diseases for Oncology (3rd edition) histologic/behavior codes were used to classify patients with RCC. 9 Only microscopically confirmed cases of RCC were included. To avoid synchronous bilateral tumors having staged surgical management, patients were excluded if their second diagnosis was within 1 year of primary diagnosis or if follow-up time was less than 12 months.…”
Section: Methodsmentioning
confidence: 99%
“…Only patients with clear cell (ccRCC) (histologic code 8310 and 8312) [8,9], chromophobe (chRCC) (histologic code 8317) [10] and papillary (pRCC) (histologic code 8260) [11] histology were considered. All were surgically treated with either partial or radical nephrectomy.…”
Section: Study Cohortsmentioning
confidence: 99%